Peningkatan Kompetensi Mahasiswa Calon Guru Sekolah Dasar dalam Pengajaran Bahasa Inggris Melalui Simulasi Interaktif Berbasis Kelompok - Isnaini Eddy Saputro (SEED: Journal of Scientific Research, 2025)
English proficiency is an essential skill for prospective elementary school teachers in the global era. This community service program aimed to enhance students’ competence in teaching English through interactive, group-based teaching simulations. Conducted over five months, the program engaged students in planning, delivering, reflecting on, and evaluating simulated lessons. Each group alternated roles as teachers and students, using contextual themes such as “Let’s Go to the Zoo.” Supervising lecturers provided feedback based on a teaching rubric covering pedagogical and linguistic aspects. The results showed significant improvement in students’ ability to design and deliver communicative English lessons, as well as increased readiness for teaching practicum. Additionally, the activity offered academic benefits for lecturers through documented practices that can be developed into teaching modules or scholarly publications. This program demonstrated that simulation is an effective strategy for strengthening the professional teaching skills of future elementary educators.